2010
DOI: 10.1159/000310940
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Migraine, Probable Migraine and Tension-Type Headache in the Croatian Population

Abstract: Background/Aim: Population-based epidemiological studies about headaches, especially migraine, have been carried out in many countries. The aim of this study was to assess the 1-year prevalence of migraine, probable migraine and tension-type headache (TTH) in the Croatian population. Methods: The design of the study was a cross-sectional survey of an adult population sample using a self-completed questionnaire. Results: The 1-year crude prevalence of migraine without and with aura in this study was 7.5%, of pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

16
27
1
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(46 citation statements)
references
References 77 publications
16
27
1
2
Order By: Relevance
“…In European countries, the past-year prevalence of dTTH ranges from 5.1 % in Eastern Europe [8] to 74.0 % in Western Europe [9]. Our results are in agreement with those of Vukovic et al, who in Croatia found a dTTH prevalence of 21.2 %, 23.2 % in women and 19.1 % in men [10]. They are not much different, either, from those recently reported by Ayzenberg et al [11], who in Russia observed a prevalence of 25.4 % for definite episodic TTH.…”
Section: Discussionsupporting
confidence: 92%
“…In European countries, the past-year prevalence of dTTH ranges from 5.1 % in Eastern Europe [8] to 74.0 % in Western Europe [9]. Our results are in agreement with those of Vukovic et al, who in Croatia found a dTTH prevalence of 21.2 %, 23.2 % in women and 19.1 % in men [10]. They are not much different, either, from those recently reported by Ayzenberg et al [11], who in Russia observed a prevalence of 25.4 % for definite episodic TTH.…”
Section: Discussionsupporting
confidence: 92%
“…So they found a lower rate for migraine but a higher rate for TTH in comparison to our results. Another study from Croatia located also in the eastern bank of Europe reported a crude and lower prevalence of TTH as 21.2% [32]. It is interesting to note that both of these studies also showed relatively low prevalence rates of TTH, like in our study.…”
Section: Discussionsupporting
confidence: 80%
“…It has been reported that the vast majority of headaches are migraine and tension-type headache (TTH). [1][2][3][4][5][6][7][8][9][10][11] Migraine is a neurovascular disorder in which cortical spreading depression, neurogenic inflammation, and cranial vascular contractile dysfunction are shared in its pathophysiology. For migraine with aura (MA), reduction in cerebral blood flow is associated with depolarization wave that propagates across the brain cortex (cortical spreading depression).…”
Section: Introductionmentioning
confidence: 99%
“…1-6, 8-11, 13 Migraine can affect people at any age but its highest prevalence was reported between ages of 35-45 years regardless of gender. [8][9][10][11]13 However, during the most reproductive years, the prevalence of migraine was reported to be threefold higher in women than in men. [13][14][15] Migraine is common in all ethnic groups.…”
Section: Introductionmentioning
confidence: 99%